Do training load metrics agree? A comparison of session rate of perceived exertion, physiological and biomechanical load in outdoor running - Scheltinga, B. L.; Buurke, J. H.; Kok, J. N.; Reenalda, J. (Sports Medicine - Open, 2026)
Background Monitoring training load is an important aspect of optimizing performance and preventing overuse injuries in runners. This is the first study comparing physiological, biomechanical and subjective load between typical outdoor training sessions, contributing to the transfer of methodologies from the gait laboratory to real-world conditions with the final goal of improving athlete monitoring.